Le Coureur des Bois (1850) de Gabriel Ferry et Der Waldläufer (1879) de Karl May : l’histoire d’un transfert franco-allemand - Herta-Luise Ott (Strenae)
In 1879, when Karl May adapted one of the many existing translations of Gabriel Ferry's novel, Le Coureur des bois (1850), in Germany, he made a whole slew of changes—from the novel’s incipit and more condensed action, to simplifying relationships between the characters and the world—which already foreshadowed the author's favorite characters to come, the Apache Winnetou and his companion Old Shatterhand, and their very particular situation.